2018
DOI: 10.1371/journal.pone.0200365
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers and predictors for functional and anatomic outcomes for small gauge pars plana vitrectomy and peeling of the internal limiting membrane in naïve diabetic macular edema: The VITAL Study

Abstract: PurposeWe aimed to investigate biomarkers and predictive factors for visual and anatomical outcome in patients with naïve diabetic macular edema (DME) who underwent small gauge pars plana vitrectomy (PPV) with internal limiting membrane (ILM) peeling as a first line treatment.DesignMulticenter, retrospective, interventional study.Participants120 eyes from 120 patients with naïve DME treated with PPV and ILM peeling with a follow up of 24 months.MethodsChange in baseline best corrected visual acuity (BCVA) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 40 publications
3
48
0
8
Order By: Relevance
“…Studies have confirmed the efficacy of vitrectomy with ILM peeling in the treatment of DME [20,21]. However, whether the removal of the ILM can resolve macular edema and improve vision remains controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have confirmed the efficacy of vitrectomy with ILM peeling in the treatment of DME [20,21]. However, whether the removal of the ILM can resolve macular edema and improve vision remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…The need for combined ILM peeling in patients with DME, however, is currently controversial. A large number of studies have shown that vitrectomy combined with internal membrane peeling is conducive to the recovery of macular edema and improved vision [10]. For simple vitrectomy or vitrectomy with internal limiting membrane peeling, it is impossible to determine the macular state before surgery because of the complexity of the fundus in patients with PDR, such as those with severe vitreous haemorrhage or tractional retinal detachment.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, comparing the evolution of hard exudates, macular edema, and visual results between surgical and medical treatments based on OCT remains a clinically relevant and important concern. Several OCT biomarkers such as inner segment-outer segment (IS-OS) layer, external limiting membrane layer, choroidal thickness, submacular fluid, hyper-reflective foci, and disorganization of retinal inner layers have been identified for DME treated with anti-VEGF, dexamethasone implant, or vitrectomy [ 45 48 ]. It is difficult to analyze the morphology and thickness of the choroid using spectral-domain OCT (SD-OCT), which was used in the present study, compared with enhance depth imaging SD-OCT or swept-source OCT.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that vitrectomy has long-term benefits for diffuse DME [12][13][14], even for those without a thickened and taut posterior hyaloid [15][16][17]. In addition, vitrectomy combined with internal limiting membrane (ILM) peeling has shown favorable anatomical and functional outcomes [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Optic nerve degeneration is also regarded as a cause of visual impairment [2][3][4][5][6][7][8]. Therefore, it is critical to identify risk factors of visual impairment to prevent occurrence of ocular vascular abnormalities and optic nerve degeneration among middle-aged or older individuals with the use of images and biomarkers [9][10][11].…”
Section: Introductionmentioning
confidence: 99%